Model investigation of temperature and concentration dependent luminescence of erbium-doped tellurite glasses - Ghoshal, S. K. (American Institute of Physics, 2011)
Improving the up-conversion efficiency is the key issue in tellurite glasses. The quantum efficiency, radiative transition rate and lifetimes of excited states are greatly influenced by the optical properties of the host material, ligand field, multiphonon relaxation processes, impurities, temperature and concentration of erbium ions. We develop a comprehensive 4-level model to examine the radiative and nonradiative (NR) decay processes for the green (4S3/2?4I15/2)(4S3/2?4I15/2) and red (4F9/2?4I15/2)(4F9/2?4I15/2) emission over a temperature range of (10–340 K) and concentration range of (0.1–4.5 mol.%). Concentration dependent enhancement and thermal quenching of efficiency for up-conversion is investigated using the derived rate equations. These features are attributed to the NR energy transfer processes, trapped impurity effects, and thermal assisted hopping. The unusual nature of temperature and concentration dependent quenching effects for green and red emission is queries for further investigations. It is further suggested that to achieve higher infrared to visible up-converted efficiency in tellurite glasses the NR channels for energy and charge transfer by phonon and impurity mediated process has to be minimized. Our results on pump power dependent emission intensity, quantum efficiency, luminescence intensity, radiative lifetimes, and transition probabilities are in conformity with other experimental findings.